The relationship between organisational culture, job satisfaction and turnover intention at an institution of higher education - Maseko, Nomvula Valencia (My University, 2019)
The general aim of this study is to determine the relationship between organisational culture, job satisfaction and turnover intention at an institution of higher education in South Africa. A quantitative, cross-sectional survey design was used in which self- administered questionnaires were utilised to collect data from a convenience sample of 198 participants. The respondents comprised mainly of the academic employees of the institution. Descriptive and inferential statistics including correlation and regression analyses were conducted. The data was collected using three different structured questionnaires. The findings indicated that there is a positive relationship between the dominant organisational culture and job satisfaction. There is a significant negative relationship between job satisfaction and turnover intention. This study recommended that every institution should figure out the effective retention strategies which may have the most impact on their employees and find ways to improve employee job satisfaction.
Thesis(M.Com.(Human Resource Management)) -- University of Limpopo, 2019
Keywords: Organisational culture; Higher education institution; Job satisfaction and turnover intention; Job satisfaction; Labor turnover